1982
DOI: 10.1128/jcm.15.4.688-702.1982
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic study of Clostridium species

Abstract: Polyacrylamide gel electrophoretic analyses of soluble cellular proteins (without sodium dodecyl sulfate) of 70 Clostridium species indicated that the procedure was readily applicable to the differentiation of species in the genus. The protein patterns correlated well with the available DNA homology data and with most accepted differential tests. Results indicated that several earlier names for species were synonyms of those of accepted species and that two accepted species may be synonymous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The isolates produced acids in PYG broth in the following decreasing order of concentration: acetic, butyric, lactic, formic, and succinic. The electrophoretic pattern of proteins (Cato et al, 1982) of cells grown in BHI broth plus Tween and NaHCO, was similar for all isolates (data not shown). This electrophoretic pattern, when compared to previously described reference strains of Clostridium species (Cato et al, 1982), was most similar to C. t&urn.…”
Section: Resultsmentioning
confidence: 74%
“…The isolates produced acids in PYG broth in the following decreasing order of concentration: acetic, butyric, lactic, formic, and succinic. The electrophoretic pattern of proteins (Cato et al, 1982) of cells grown in BHI broth plus Tween and NaHCO, was similar for all isolates (data not shown). This electrophoretic pattern, when compared to previously described reference strains of Clostridium species (Cato et al, 1982), was most similar to C. t&urn.…”
Section: Resultsmentioning
confidence: 74%
“…This view is supported by the high degree of cultural, biochemical and SDS-PAGE similarity between six Australian isolates and two exotic strains of A. salmonicida isolated from goldfish. SDS-PAGE analysis of bacterial protein provides highly sensitive and reproducible phenotypic characterisation of bacteria (Cato, Hash.. Holeman & Moore 1982) and is a powerful technique for verifying the identity of bacteria (Moore, Hash, Holeman & Cato 1980). The similar protein profiles of the A. salmonicida strains indicated that the strains were very closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble protein profiles. The polyacrylamide slab gel electrophoresis procedure described by Moore et al (30) and Cato et al (5) was used to compare soluble cellular proteins from overnight cultures in brain heart infusion-Tween-carbonate broth (30). As controls, Streptococcus faecalis strain VPI U4-20 and C. difficile strains VPI 8491 (ATCC %89) and VPI 10463 were included.…”
Section: Louis Mo) (8)mentioning
confidence: 99%